Evaluation of methylated DCR1 as a biomarker for response to adjuvant irinotecan-based therapy in stage III colon cancer: cancer and leukaemia Group B 89803 (Alliance). Issue 12 (2nd December 2022) - Symonds, Lynn; Yu, Ming; Zhang, YuHong; Ou, Fang-Shu; Zemla, Tyler J.; Carter, Kelly; Bertagnolli, Monica; Innocenti, Federico; Bosch, Linda JW; Meijer, Gerrit A; Carvalho, Beatriz; Grady, William M.; et al.
ABSTRACT: Aberrantly methylated genes contribute to the landscape of epigenetic alterations in colorectal adenocarcinoma. The global CpG Island methylator phenotype (CIMP) and individually methylated genes are potential prognostic/predictive biomarkers. Research suggests an association between methylated DCR1 (m DCR1 ) and lack of benefit with irinotecan (IFL) treatment. We assessed the association between DCR1 methylation status and survival in patients receiving adjuvant fluorouracil/ leucovorin (5-FU/LV) or IFL. We analysed data from patients with stage III colon adenocarcinoma randomly assigned to adjuvant 5-FU/LV or IFL in CALGB 89803 (Alliance). The primary endpoint was overall survival (OS), and the secondary endpoint was disease-free survival (DFS). Using tumour sample DNA, we evaluated the association between survival, DCR1 methylation status, and molecular subgroups ( BRAF, KRAS, mismatch repair status, CIMP status) using Kaplan–Meier estimator and Cox proportional hazard model. m DCR1 was observed in 221/400 (55%) colon cancers. Histopathologic features were similar between m DCR1 and unmethylated DCR1 (un DCR1 ) colon cancers. There was no difference in OS ( p = 0.83) or DFS ( p = 0.85) based on DCR1 methylation status. There was no association between methylation status and response to IFL . In patients with un DCR1 and KRAS -wildtype tumours, those who received IFL had a nearly two-fold worse DFS compared to patients who received 5-FU/LV (HR = 1.85, 95% CI (0.97–3.53, p = 0.06). This relationship was not notable among other subgroups. In stage III colon cancer patients, m DCR1 status did not associate with response to irinotecan. Larger studies may suggest an association between the iridocene response and molecular subgroups.